Developing treatments for rhodopsin-related dominant retinitis pigmentosa - Orlans, H (2019)
Mutations in the rhodopsin gene are one of the most common causes of autosomal dominant retinitis pigmentosa (ADRP) and there is at present no treatment available. In this thesis, three potential treatments were developed and tested in a RhoP23H/+ knock-in mouse model. In the first, animals were housed in red cages which acted as long-pass light filters. This resulted in a significant slowing in the rate of both rod and cone photoreceptor degeneration as determined anatomically using non-invasive in vivo imaging and immunohistochemistry, and functionally by dark- and light-adapted electroretinography. In the second, efficient adeno-associated viral (AAV) vectors expressing wild type human rhodopsin were manufactured and injected subretinally in RhoP23H/+ mice to test the hypothesis that overexpression of the normal protein might overcome the effect of the P23H mutant. No structural or functional rescue effect was however observed. The final treatment strategy involved development of artificial mirtrons to suppress expression of endogenous rhodopsin. Mirtrons are novel RNA interference effectors that are spliced from mRNA transcripts. Both efficient mirtrons and a codon modified mirtron-resistant version of the human rhodopsin coding sequence were designed and validated in vitro. These elements were then combined under the control of a single rhodopsin promoter within AAVs as knockdown/replacement gene therapy vectors for ADRP. Subretinal injection in the RhoP23H/+ mouse resulted in mouse-to-human rhodopsin mRNA replacement, and this was associated with a modest rescue effect when injected at a dose of 2x108 gc. This represents the first use of an artificial mirtron to induce gene knockdown in vivo.